Proceedings of the Mathematics, Informatics, Science, and Education International Conference (MISEIC 2018) 2018
DOI: 10.2991/miseic-18.2018.34
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking Skill of High-Performance Mathematics Teacher in Solving Mathematical Problem

Abstract: This study aims to describe the critical thinking skill of high performance mathematics teacher in solving mathematical problems with the subject was a junior high school teacher who was awarded as a high performance teacher. Qualitative research method was used to reveal the critical thinking skill of a high performance mathematics teacher, data collection gathered through in-depth interviews based on mathematical problem solving tasks. The results indicate that critical thinking skill of high performance mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Cahyono et al, 2019;Budi Cahyono, 2017;Fitriani et al, 2018;Shubina & Kulakli, 2019). Kemampuan berfikir kritis peserta didik dalam memecahkan masalah dipengaruhi oleh kemampuan matematika (Anjariyah et al, 2018;Jacob, 2012). Beberapa penelitian melalui indikator baru yang dibangun berupaya mendeskribsikan pemikiran kritis siswa dan menggunakannya dalam pelevelan (Paul & Elder, 2008;Rasiman, 2008).…”
Section: Pendahuluanunclassified
“…Cahyono et al, 2019;Budi Cahyono, 2017;Fitriani et al, 2018;Shubina & Kulakli, 2019). Kemampuan berfikir kritis peserta didik dalam memecahkan masalah dipengaruhi oleh kemampuan matematika (Anjariyah et al, 2018;Jacob, 2012). Beberapa penelitian melalui indikator baru yang dibangun berupaya mendeskribsikan pemikiran kritis siswa dan menggunakannya dalam pelevelan (Paul & Elder, 2008;Rasiman, 2008).…”
Section: Pendahuluanunclassified
“…For example, there are still various problems related to critical thinking ability, mathematical anxiety, mathematics interest, negative self-perception, etc. For example, there are still errors in the critical thinking process in solving mathematical problems (Anjariyah et al, 2018). found that a significant negative impact on mathematics performance was caused by the prospective math teachers' high degree of male and female math anxiety.…”
Section: Introductionmentioning
confidence: 99%